24- and 36-Week Outcomes for the Child/Adolescent Anxiety Multimodal Study (CAMS) - Piacentini, John (2013)
OBJECTIVE: We report active treatment group differences on response and remission rates and changes in anxiety severity at weeks 24 and 36 for the Child/Adolescent Anxiety Multimodal Study (CAMS). METHOD: CAMS youth (N=488; 74%≤12 years) with DSM-IV separation, generalized, or social anxiety disorder were randomized to 12 weeks of cognitive behavior therapy (CBT), sertraline (SRT), CBT+SRT (COMB), or medication management/pill placebo (PBO). Responders attended 6 monthly booster sessions in their assigned treatment arm; youth in COMB and SRT continued on their medication throughout this period. Efficacy of COMB, SRT, and CBT (N=412) was assessed at 24 and 36 weeks postrandomization. Youth randomized to PBO (n=76) were offered active CAMS treatment if nonresponsive at week 12 or over follow-up and were not included here. Independent evaluators blind to study condition assessed anxiety severity, functioning, and treatment response. Concomitant treatments were allowed but monitored over follow-up. RESULTS: Most (>80%) acute responders maintained positive response at both weeks 24 and 36. Consistent with acute outcomes, COMB maintained advantage over CBT and SRT, which did not differ, on dimensional outcomes; the 3 treatments did not differ on most categorical outcomes over follow-up. Compared to COMB and CBT, youth in SRT obtained more concomitant psychosocial treatments, while those in SRT and CBT obtained more concomitant combined (medication plus psychosocial) treatment. DISCUSSION: COMB maintained advantage over CBT and SRT on some measures over follow-up, while the 2 monotherapies remained indistinguishable. The observed convergence of COMB and monotherapy may be related to greater use of concomitant treatment during follow-up among youth receiving the monotherapies, although other explanations are possible. While outcomes were variable, most CAMS-treated youth enjoyed sustained treatment benefit. Clinical trial registration information— Child and Adolescent Anxiety Disorders (CAMS); http://clinicaltrials.gov; NCT00052078.